Five-year overall survival of pembrolizumab in advanced non-small cell lung cancer: another step from care to cure? - Bironzo, Paolo; Passiglia, Francesco; Novello, Silvia (Annals of Translational Medicine, 2019)
Immune checkpoint inhibitors (ICIs) directed against programmed cell death protein 1(PD-1) and its ligand (PD-L1) have rapidly changed non-small cell lung cancer (NSCLC) treatment paradigms, leading to unprecedented results, both in metastatic and locally advanced disease.